ANALISIS NERACA AIR DI TITIK BENDUNG TEMPANG DAERAH IRIGASI PANASEN HULU KABUPATEN MINAHASA - Turangan, Regia; Mananoma, Tiny; Sumarauw, Jeffry S.F. (STKIP PGRI Situbondo, 2024)
This study aims to conduct a water balance analysis at the Tempang weir point, which is part of the Panasen Hulu Irrigation Area in Minahasa Regency. The Panasen River is the main source of water to meet the irrigation needs in this area. Given the complexity of the dry season period which is difficult to predict, water balance analysis needs to be carried out to calculate the availability and demand of water in the Upper Panasen Irrigation Area, to improve the optimization of water resource management of the Panasen River. Water balance analysis is carried out by calculating the ratio between water availability and water demand. To calculate water availability, the NRECA Modified method is used with available data, namely rainfall data, evapotranspiration, and watershed parameters to calculate the mainstay discharge Q80% and water availability for maintenance of the Q95% River. The calculated water needs are for water needs in the Upper Panasen Irrigation Area. The results of the water balance analysis show periods of water deficit in which water demand exceeds water availability, causing difficulties in meeting irrigation needs. However, there are also periods of surplus water that can be utilized for more effective management of water resources.